Rozdily a podobnosti v technikach zpevu klasickeho a popularniho - Chladova, Marketa (Aura musica, 2024)
The art of singing can be divided in terms of style and origins in two main different categories: classical singing technique or contemporary commercial singing technique. The singing technique should be used with regard to the character and style of the particular interpreted composition.
Keywords: contemporary commercial singing; singing technique; contemporary commercial music; vocal registers